The influence of cyclists' competitive level and exercise intensity on crank torque variability during pedalling - Herrero-Molleda, A.; Floría, P.; Garcia-Lopez, J. (ISBS Proceedings Archive (Michigan), 2021)
The purpose of this study was to analyse the influence of competitive level and pedalling intensity on crank torque variability. Seventy-two cyclists (Club, Elite, Professional) pedalled at 200, 250 and 300 W on a cycle ergometer that recorded crank torque. Multiple-trial variability (average standard deviation) and complexity (Sample Entropy) analyses were applied. Both competitive level and pedalling intensity showed a significant effect on Sample Entropy values of crank torque, with a significant interaction between the two factors, while average standard deviation was only affected by pedalling intensity. In conclusion, pedalling intensity had an effect on both crank torque multiple-trial variability and complexity, while the last has shown a bigger potential for fine discrimination between performance levels in cyclists.